Effect of individual spinal muscle activities on upright posture using a human body finite element model - Yuko Nakahira; Masami Iwamoto; Tatsuya Igawa; Ken Ishii (Scientific Reports)
Abstract The occurrence of diseases characterized by irregular spinal alignment, such as kyphosis, lordosis, scoliosis, and dropped head syndrome (DHS) is increasing, particularly among older adults. DHS is characterized by an excessive forward tilt of the head and neck, causing the head to droop. Although it is believed that muscle activity plays a role in both the onset and treatment of DHS, the underlying mechanisms remain unclear. To elucidate the mechanism, we used a human body finite element model, which included the erector spinae muscle group, and a muscle controller with fixed legs for spinal posture stabilization. The model replicated muscle activation levels during the maintenance of an upright posture under gravity, similar to those obtained from experimental data. Parametric simulations to investigate the effect of each spinal muscle impairment on upright posture with and without compensatory activities of the other muscles suggest that trunk extensors; the multifidus L1-S and longissimus thoracis muscles, and hip flexors; psoas major and iliacus muscles play an integral role in maintaining an upright posture. These findings support the results of a rehabilitation study that reported that exercises targeting the trunk, psoas muscles, and cervical extensors could improve global spinal alignment and clinical outcomes in DHS.